2014
DOI: 10.1007/jhep12(2014)154
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of effective theory for multiple M5-branes compactified on circle

Abstract: A supersymmetric non-Abelian self-dual gauge theory with the explicit introduction of Kaluza-Klein modes is proposed to give a classical description of multiple M5-branes on R 5 × S 1 . The gauge symmetry is parametrized by Lie-algebra valued 1-forms with the redundancy of a 0-form, and the supersymmetry transformations without gaugefixing are given. We study BPS configurations involving KK modes, including M-waves and M2-branes with non-trivial distributions around the circle. Finally, this supersymmetric gau… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 119 publications
0
15
0
Order By: Relevance
“…We compare our results with the theory given in [1]. This case is of particular interest for physics, since it can be related to the multiple M5-brane system compactified on S 1 [1,8,10]. In section 5, we discuss the n = 5 case.…”
Section: Jhep07(2016)125mentioning
confidence: 96%
See 2 more Smart Citations
“…We compare our results with the theory given in [1]. This case is of particular interest for physics, since it can be related to the multiple M5-brane system compactified on S 1 [1,8,10]. In section 5, we discuss the n = 5 case.…”
Section: Jhep07(2016)125mentioning
confidence: 96%
“…From these investigations we understand that there are two main obstructions to obtain a local action with manifest Lorentz symmetry [7,8,10]. One originates from the difficulty to formulate the theory with nontrivially interacting tensor field and the other is the difficulty to construct the action for the self-dual tensor field [11][12][13][14].…”
Section: Jhep07(2016)125mentioning
confidence: 99%
See 1 more Smart Citation
“…The gauge symmetry in 5d has an interesting non-Abelian gerbe structure [1], [2], [4]. In the simplest set-up where all the fields transform in the adjoint representation, the gauge symmetry variations are…”
Section: The Non-abelian Gerbementioning
confidence: 99%
“…Another proposal has been to add a KK tower of fundamental field excitations to the 5d SYM. It has been shown that this can be done while preserving the 6d (1, 0) Poincare supersymmetry in flat space with one compact circle direction [11], [6], [14], [15]. In this paper, we will generalize this construction and consider six-manifolds that are circlebundles.…”
Section: Introductionmentioning
confidence: 99%